The use of intravoxel incoherent motion in differentiation between benign and malignant BI-RADS 4 (or above) breast lesions combined with abbreviated MRI sequence in comparison with the histopathology - Mohamed Karam Samak; Salma Hassan Tantawy; Amal Ibrahim Ahmed Othman (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background The incidence of breast cancer (BC) has increased dramatically and has passed lung cancer as the most common malignant tumor worldwide, with an average estimation of over 2 million new cases added every year. The diagnostic pathway of any breast lumps starts with clinical examination followed by sonomammography examination and classifies the lesion according to Breast imaging reporting and data system (BI-RADS) score developed by ACR into seven grades (0: 6) with BI-RADS 4 lesions which are considered suspicious, yet have no full criteria of malignancy with probability of malignancy (2%: 94%), so biopsy is considered to define the nature of the lesion. Aim of the work To assess the value of intravoxel incoherent motion technique based on diffusion-weighted imaging (DWI-IVIM) sequence for antegrade identification of benignity and malignancy of BI-RAD 4 or above lesions and correlation to the histopathology findings as a gold standard. Methods Prospective study was conducted for female patient aged (25: 80) presented for tru-cut biopsy with sonomammography lesion classified as BI-RADS 4 or above; she underwent an abbreviated MRI sequence with IVIM. Type of research Prospective study. Results Our study analyzed the role of DWI-IVIM in identifying the benignity and malignancy of BI-RADS 4 lesions or above detected on sonomammography during screening. By combining the data from the IVIM sequence (quantitative variables), this study concludes that ADC_Mean, ADC_Max, D*_Mean, and D*_Max can be used to differentiate the benignity and malignancy of the BI-RADS 4 lesions or above in the lack of contrast which can help to avoid patient unnecessary exposure to contrast risk and unnecessary breast biopsy, especially in BI-RADS 4a as seen from our results, we could reach a ADC_Mean, ADC_Max cut-off values 1.27 × 10−3 1.49 × 10−3, respectively, with sensitivity and specificity about 100%, 56.25% a ADC_Mean and 100, 62.5% for ADC_Max. Conclusions Some IVIM parameters could represent a reliable tool for further assessment of BI-RADS 4 breast lesion to avoid unnecessary biopsy, especially if combined with sonomammography, yet it needs proper standardization of the b-values, ROI (region of interest) and post-processing process.